The Influence of Profitability, Dividend Policy, and Capital Structure on Company Value - Siti S Kandita; Nufzatutsaniah Nufzatutsaniah (Indonesian Development of Economics and Administration Journal, 2025)
This study aims to determine the influence of Profitability, Dividend Policy, and Capital Structure on Firm Value at PT Industri Jamu dan Farmasi Sidomuncul Tbk during the period 2013-2022, both partially and simultaneously. The financial ratios examined include Return on Assets, Dividend Payout Ratio, Debt to Equity Ratio, and Price to Book Value. The object of this research is PT Industri Jamu dan Farmasi Sidomuncul Tbk, with secondary data sourced from annual financial reports over the period 2013-2022. The research method used is a quantitative approach, with data collection techniques utilizing documentation methods. Data analysis is performed using descriptive methods, t-tests, F-tests, and Adjusted R-square determination tests. The results of the study indicate that, partially, the Debt to Equity Ratio has a significant influence on Price to Book Value, while Return on Assets and Dividend Payout Ratio do not have a significant influence. Simultaneously, there is a significant influence among Return on Assets, Dividend Payout Ratio, and Debt to Equity Ratio on Price to Book Value. The Adjusted R-square coefficient of determination shows that 87.8% of the variation in Price to Book Value can be explained by these three variables, while the remaining 12.2% is influenced by other variables outside this study.